Semitendinosus and Gracilis Autograft for Neglected Patellar Tendon Rupture: A Surgical Reconstruction - Adisthanaya, Surya; Astawa, Putu; Aryana, I Gusti Ngurah Wien; Febyan (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Neglected patellar tendon rupture is an extremely rare case among orthopedic injuries that severely compromises the function of the extensor mechanism of the knee. Therefore, a prompt and accurate diagnosis of a ruptured patellar tendon are a key to efficacious management, because a treatment delay is often associated with unsatisfactory functional outcomes. CASE PRESENTATION: We report the case of an adult male patient with traumatic patellar tendon rupture after 9 months of a motorcycle accident. The patient underwent reconstruction surgery using semitendinosus and gracilis tendon augmentation. This procedure restores the anatomical position of the patella and prevents extensor lag. At a 3-month follow-up, a full recovery of the structure and function of the extensor mechanism was perceived. The patient could return to normal daily activities following rehabilitation protocol. CONCLUSION: Semitendinosus and gracilis tendon autograft is the technique of choice to be applied in the surgical reconstruction of neglected patellar tendon rupture.